d(−) Lactic Acid-Induced Adhesion of Bovine Neutrophils onto Endothelial Cells Is Dependent on Neutrophils Extracellular Traps Formation and CD11b Expression - Pablo Alarcón; Carolina Manosalva; Carolina Manosalva; Ivan Conejeros; María D. Carretta; Tamara Muñoz-Caro; Liliana M. R. Silva; Anja Taubert; Carlos Hermosilla; María A. Hidalgo; Rafael A. Burgos (Frontiers in Immunology, 2017)
Bovine ruminal acidosis is of economic importance as it contributes to reduced milk and meat production. This phenomenon is mainly attributed to an overload of highly fermentable carbohydrate, resulting in increased d(−) lactic acid levels in serum and plasma. Ruminal acidosis correlates with elevated acute phase proteins in blood, along with neutrophil activation and infiltration into various tissues leading to laminitis and aseptic polysynovitis. Previous studies in bovine neutrophils indicated that d(−) lactic acid decreased expression of L-selectin and increased expression of CD11b to concentrations higher than 6 mM, suggesting a potential role in neutrophil adhesion onto endothelia. The two aims of this study were to evaluate whether d(−) lactic acid influenced neutrophil and endothelial adhesion and to trigger neutrophil extracellular trap (NET) production (NETosis) in exposed neutrophils. Exposure of bovine neutrophils to 5 mM d(−) lactic acid elevated NET release compared to unstimulated neutrophil negative controls. Moreover, this NET contains CD11b and histone H4 citrullinated, the latter was dependent on PAD4 activation, a critical enzyme in DNA decondensation and NETosis. Furthermore, NET formation was dependent on d(−) lactic acid plasma membrane transport through monocarboxylate transporter 1 (MCT1). d(−) lactic acid enhanced neutrophil adhesion onto endothelial sheets as demonstrated by in vitro neutrophil adhesion assays under continuous physiological flow conditions, indicating that cell adhesion was a NET- and a CD11b/ICAM-1-dependent process. Finally, d(−) lactic acid was demonstrated for the first time to trigger NETosis in a PAD4- and MCT1-dependent manner. Thus, d(−) lactic acid-mediated neutrophil activation may contribute to neutrophil-derived pro-inflammatory processes, such as aseptic laminitis and/or polysynovitis in animals suffering acute ruminal acidosis.